2020
DOI: 10.3847/1538-4357/ab7666
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Chirality, Sense of Rotation, and Hemispheric Preference of Solar Eruptive Filaments

Abstract: The orientation, chirality, and dynamics of solar eruptive filaments is a key to understanding the magnetic field of coronal mass ejections (CMEs) and therefore to predicting the geoeffectiveness of CMEs arriving at Earth. However, confusion and contention remain over the relationship between the filament chirality, magnetic helicity, and sense of rotation during eruption. To resolve the ambiguity in observations, in this paper, we used stereoscopic observations to determine the rotation direction of filament … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 47 publications
4
31
0
Order By: Relevance
“…Meanwhile, during its eruption, the apex part of the filament displays CCW rotation, which can be seen in both SDO and STEREO-A observations (Figure 2(b),(d), and accompanied anima-tion). This event is a well-observed example supporting a strong one-to-one relationship during the eruption as found by Zhou et al (2020); sinistral/dextral filaments rotate clockwise (CW)/counterclockwise (CCW) when viewed from above, and the morphology of the filament and related sigmoid both exhibit a forward (reverse) S shape.…”
Section: Observation Of a Typical Filament Eruptionsupporting
confidence: 77%
See 2 more Smart Citations
“…Meanwhile, during its eruption, the apex part of the filament displays CCW rotation, which can be seen in both SDO and STEREO-A observations (Figure 2(b),(d), and accompanied anima-tion). This event is a well-observed example supporting a strong one-to-one relationship during the eruption as found by Zhou et al (2020); sinistral/dextral filaments rotate clockwise (CW)/counterclockwise (CCW) when viewed from above, and the morphology of the filament and related sigmoid both exhibit a forward (reverse) S shape.…”
Section: Observation Of a Typical Filament Eruptionsupporting
confidence: 77%
“…Indeed, observations of filament eruptions show that there is a one-to-one correlation between the rotation direction and the filament chirality (or sign of helicity of the corresponding mag-netic field); sinistral (dextral) filaments with positive (negative) helicity rotate clockwise (counterclockwise) when viewed from above (Green et al 2007). Furthermore, the pre-eruptive morphology of filaments corroborates an moderate hemispheric preference, namely, filaments of forward (reverse) S shape are usually located in the southern (northern) hemisphere and have a positive (negative) helicity (Rust & Kumar 1996;Zhou et al 2020). Besides, there are coronal loops presenting S shape known as sigmoids observed in extreme ultraviolet (EUV) and soft X-ray (SXR) passbands (Cheng et al 2017), and in many events the sigmoid is found to be co-spatial roughly with the pre-eruptive filament.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Alternatively, Chen et al (2014) proposed that a filament is dextral (sinistral) if during the eruption the conjugate sites of plasma draining are right-skewed (left-skewed) with respect to the PIL. Employing this new criteria, it is found that the hemispheric rule of filament chirality is significantly strengthened (Ouyang et al 2017;Zhou et al 2020b).…”
Section: Filamentsmentioning
confidence: 99%
“…However, 2D images might cheat our eyes as demonstrated by a famous animation picture, where a dancing girl can be recognized to rotate clockwise or counterclockwise. In this sense, 3D construction of the filament shapes and motions based on stereoscopic or spectroscopic observations are important (Li et al 2010b(Li et al , 2011Song et al 2018;Zhou et al 2020b). -Allowance height: Observations indicated that most prominences have an upper edge below 50 Mm, and the maximum height of the upper edge of quiescent prominences is ∼500 Mm (Wang et al 2010).…”
Section: Prospects Of Other Topicsmentioning
confidence: 99%